Stability Monitoring and Analysis of High and Steep Slope of a Hydropower Station - Guangcheng Shi; Gongkai Gu; Hua Zhou; Zhigang Tao; Hongyue Pan; Ting Tang (Geofluids)
Slope deformation and failure are major challenges for hydropower station engineering. Taking the left bank slope at the exit of the flood discharge tunnel of the Wudongde Hydropower Station in China as an example, the deformation mechanism of the high-steep rock slope was studied. The height of the slope is about 200 m, which is affected by slope excavation, rainfall, and atomized rain. The results of multipoint displacement meters, surface deformation monitoring, and anchoring stress meters showed that the deformation and deformation rate of the slope have increased dramatically. Through the comprehensive analysis of the slope, it is found that the overall lithology of the slope is poor, the excavation disturbance causes the redistribution of the stress in the slope, and the excavation surface is relatively steep, which provides space for the deformation of the slope rock mass. Unloading relaxation leads to a large number of new fissures in the slope rock mass. These new fissures and fault fracture zones provide convenient conditions for rainfall and atomized rain infiltration. The rainwater infiltrated along the slope surface, formed the seepage field in the slope body, and weakened the rock-soil mass parameters. Meanwhile, saturated runoff is formed on the slope, causing large deformation of the slope rock mass. However, the migration of water in the slope has a time effect, and its influence on the stability of the slope also has a time effect. It is difficult for traditional monitoring methods to monitor the resulting changes in internal sliding force of the slope. Therefore, a remote monitoring and early warning system for landslide anchor cable force was introduced to monitor the slope stability changes caused by the impact of water flow and rainfall infiltration, which provided a reasonable and scientific reference for subsequent slope construction.